Can an evidence-based fall prevention program be translated for use in culturally diverse communities? - Sleet, David A.; Baldwin, Grant T. (Journal of sport and health science, 2014)
Older adult falls are a significant public health problem,but one that is amenable to preventive interventions.1,2 Despite the progress made in identifying risk factors,developing efficacious health-related interventions,and promoting evidencebased programs in the community,much work remains before these strategies are broadly available and effectively used to reduce fall-related injuries.3 As Newton and ScottFindlay4 have pointed out,the translation of basic scientific knowledge into clinical studies,and the transformation of clinical studies into improvements in health services and public health practices,remain major obstacles to widespread adoption.